Diagnostic Accuracy of Ankle-Brachial Pressure Index Compared with Doppler Arterial Waveforms for Detecting Peripheral Arterial Disease: A Systematic Review. (April 2022) - Kashetsky, Nadia; Sachdeva, Muskaan; Lu, Justin D.; Mufti, Asfandyar; Kim, Patrick; Bagit, Ahmed; Sibbald, R. Gary
Abstract : GENERAL PURPOSE: To present the results of a research study evaluating the diagnostic accuracy of the ankle-brachial pressure index (ABPI) compared with that of Doppler arterial waveforms (DAWs) to detect peripheral arterial disease (PAD). TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After completing this continuing education activity, the participant will: 1. Summarize the evidence the authors considered when comparing the diagnostic accuracy of the ABPI with that of Doppler arterial waveforms to detect PAD. 2. Select the characteristics of the participants in the studies the authors analyzed. 3. Identify the results of the authors' study comparing the diagnostic accuracy of the ABPI with that of Doppler arterial waveforms to detect PAD. 4. Distinguish the authors' conclusions about the advantages of using Doppler arterial waveforms to detect PAD. ABSTRACT: Although the ankle-brachial pressure index (ABPI) is a useful tool for the noninvasive assessment of peripheral arterial disease (PAD), it has several limitations necessitating alternative noninvasive diagnostic tools. This study assesses the diagnostic accuracy of ABPI compared with Doppler arterial waveforms (DAWs) to detect PAD. The authors searched Embase and MEDLINE for original studies that reported sensitivities and specificities for both the ABPI and DAW. Four studies were included representing 657 patients (58.8% men) with a mean age of 63.4 years. The authors detected overall higher sensitivities using DAW compared with ABPI but higher specificities with ABPI compared with DAW. In conclusion, because of the higher sensitivity and lower specificity of DAW compared with ABPI, the authors recommend DAW as a potential screening tool for PAD. To confirm these results, larger sample sizes and comparative trials with homogeneous reference standards and patient populations are required. In addition, DAW is not easily documented for everyday bedside practice in the community. With COVID-19 restrictions, an audible handheld Doppler signal may act as a reproducible equivalent to DAW and thus facilitate timely, safe application of compression therapy at point-of-care.